2018
DOI: 10.3390/diagnostics8040075
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Gastrointestinal Cancers

Abstract: Liquid biopsy is the sampling of any biological fluid in an effort to enrich and analyze a tumor’s genetic material. Peripheral blood remains the most studied liquid biopsy material, with circulating tumor cells (CTC’s) and circulating tumor DNA (ctDNA) allowing the examination and longitudinal monitoring of a tumors genetic landscape. With applications in cancer screening, prognostic stratification, therapy selection and disease surveillance, liquid biopsy represents an exciting new paradigm in the field of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
10
0
1
Order By: Relevance
“…In addition to ctDNA, other circulating tumor biomarkers such as circulating tumor cells (CTC) and exosomes might be also relevant. However, the detection rate of CTC, as reported in multiple studies [29,30,31,32], appears low in metastatic gastric cancer patients (e.g., less than half of 106 patients with advanced gastric cancer displayed ≥2 CTCs using CellSearch [33]), and precludes any clinical use in non-metastatic gastric cancer patients. Lastly, exosome detection has gained increasing interest, being potentially more sensitive than ctDNA in lung cancer [34], but only a few preliminary reports are available on gastric cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ctDNA, other circulating tumor biomarkers such as circulating tumor cells (CTC) and exosomes might be also relevant. However, the detection rate of CTC, as reported in multiple studies [29,30,31,32], appears low in metastatic gastric cancer patients (e.g., less than half of 106 patients with advanced gastric cancer displayed ≥2 CTCs using CellSearch [33]), and precludes any clinical use in non-metastatic gastric cancer patients. Lastly, exosome detection has gained increasing interest, being potentially more sensitive than ctDNA in lung cancer [34], but only a few preliminary reports are available on gastric cancers [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Western countries, where the medical costs related to endoscopic diagnosis and treatment of upper gastrointestinal disease have been estimated at up to $88 000, endoscopic screening for the general population is considered impractical ( 15 ). Blood tests and liquid biopsies or the upper gastrointestinal series are less invasive diagnostic modalities with potential, but their accuracy and efficacy remain unsatisfactory ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced identification of MRD in these patients may help better adjuvant therapy selection. Liquid biopsy has also been extensively investigated as a technique for monitoring disease recurrence, and serial profiling has enabled identification of recurrence prior to radiological imaging in patients with colorectal cancer and pancreatic cancer (3,18). Numerous studies (19,20) demonstrated a decrease in ctDNA levels in response to chemotherapy and a subsequent increase in case of treatment resistance.…”
Section: The Emerging Role Of Liquid Biopsy In Gastrointestinal Cancersmentioning
confidence: 99%
“…It has been clearly demonstrated that liquid biopsies can detect molecular changes associated with GI tumors in body fluids (3). Peripheral blood remains the most studied material for liquid biopsy as it contains viable circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) released from apoptotic or necrotic tumor cells.…”
Section: Introductionmentioning
confidence: 99%